Strengthening character value based on experiential learning to reduce student academic cheating behavior - Darmiany Darmiany; I Ketut Widiada; Khairun Nisa; Mohammad Archi Maulyda; Iva Nurmawanti (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2021)
A strong character has a very important role in many aspects of life, especially the academic field. This study aims to test the effectiveness of experiential learning on strengthening character values in reducing student academic cheating. The subjects of this study were a small group of students (38 people). The instruments used in data collection were academic fraud questionnaires and pretest-posttest questions. The data analysis technique used the Mc Nemar Test. The results of the Mc Nemar Test show that the value of Z count> Z table and a significant value> 0.05, or 3.77> 1.96, and 0.809> 0.05, thus the conclusion is that H0 is rejected. This means that the experiential learning strategy can improve the strengthening of student character and reduce academic cheating.